Social support and intergenerational contact: studying elderly patients with cognitive alterations - Bruna Moretti Luchesi; Tábatta Renata Pereira de Brito; Reijane Salazar Costa; Sofia Cristina Iost Pavarini (Universidade Federal de Goias, 2015)
The aim of this study was to investigate the relationship between social support to elderly patients with cognitive alterations in different contexts of social vulnerability and the presence of children living in the same household. A descriptive, cross-sectional study assessed 85 elderly individuals in different contexts of social vulnerability; all of them presented results below the cut-off point in the mini mental state examination. All ethical guidelines were respected. A sociodemographic and family characterization tool, the mini mental state examination, and the Medical Outcomes Study (MOS) were applied. The results showed good levels of social support received by elderly individuals and a statistically significant correlation between the extent of emotional support and the presence of children in the household (t=2.16, p<0.01). These results enable a better understanding on the relationships between elderly people and children by evidencing that intergenerational contact favors the perception of satisfactory social support by the elderly.